"Good Mothers Work": How Maternal Employment Shapes Women's Expectation of Work and Family in Contemporary Urban China. (7th August 2020) - Zhou, Yun
Abstract: Drawing on 70 in‐depth interviews, I investigated how maternal employment shapes urban young Chinese women's work–family expectation in a context of rapid social change. These interviews indicated that respondents attached strong moral meaning to mothers' wage work, regarding it as integral to a "good" mother and an "ideal" woman. This moralization of maternal employment, in turn, led contemporary young Chinese women to view wage work as a taken‐for‐granted choice. Yet different from their own mothers, these young women were confronted with profound transformation across various domains of the postreform Chinese society. The normative expectation of women's wage work, coupled with slow‐to‐change expectations about women's roles at home and in a changing labor market, intensified young women's burden of "doing it all." This research highlights the importance of bringing the macro‐level context back into the mother–daughter dyad to understand the intergenerational transmission of gender beliefs and behavior.